Researching domestic violence and abuse in healthcare settings: challenges and issues - McGarry, Julie; Ali, Parveen (SAGE, 2016)
Domestic violence and abuse (DVA) is now recognised as a significant global health and societal issue. Conducting DVA research in healthcare contexts requires the consideration and understanding of a number of practical, methodological and ethical issues. Based on their experiences of working as clinicians and researchers, the authors aim to explore some of the pertinent issues and challenges associated with DVA research conducted in healthcare settings involving patients and/or healthcare professionals or both. A number of ethical, methodological and practical challenges, particularly those associated with research design and data collection, and ethical challenges related to participants and researchers, are explored.